CUBITAL TUNNEL SYNDROME A CASE REPORT - Deleva Stoshevska, Tatjana; Stoshevski, Bojan; Nikoloska, Sofija; Nikoloski, Marko; Ristikj Stomnaroska, Daniela (Journal of Morphological Sciences, 2026)
Cubital tunnel syndrome is the second most common peripheral neuropathy of the upper extremity. It is caused by compression of the ulnar nerve at the elbow region. Cubital tunnel syndrome is a neuropathy of the ulnar nerve causing symptoms of shooting pain and numbness along the medial aspect of the forearm, including the medial half of the fourth digit and the fifth digit. We present a case report of a 47-year-old male patient, an architect by profession, who complained of left elbow and forearm pain that radiated into his hand and motor weakness in the little and ring fingers of the left hand. MRI imaging of the cervical spine showed normal findings. EMNG findings revealed compressive sensorimotor neuropathy of the left ulnar nerve, with compression at the level of the elbow joint. The patient was diagnosed with cubital tunnel syndrome, caused by compression of the ulnar nerve at the elbow. The treatment was conservative, with the use of anti-inflammatory medications and physical therapy, resulting in a good clinical outcome. Keywords: Cubital tunnel, sensorimotor neuropathy.